2018
DOI: 10.1038/s41467-018-03242-8
|View full text |Cite
|
Sign up to set email alerts
|

Item-level analyses reveal genetic heterogeneity in neuroticism

Abstract: Genome-wide association studies (GWAS) of psychological traits are generally conducted on (dichotomized) sums of items or symptoms (e.g., case-control status), and not on the individual items or symptoms themselves. We conduct large-scale GWAS on 12 neuroticism items and observe notable and replicable variation in genetic signal between items. Within samples, genetic correlations among the items range between 0.38 and 0.91 (mean rg = .63), indicating genetic heterogeneity in the full item set. Meta-analyzing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
274
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(295 citation statements)
references
References 61 publications
18
274
2
1
Order By: Relevance
“…rs11682175 achieves high PIPs with annotation in both loci (0.999 and 0.864 in rs75575209 and rs7596038, respectively) (Table S12). While not reported in the CLOZUK GWAS, rs11682175 has been significantly associated with major depression (Wray et al 2018), neuroticism (Nagel et al 2018), and schizophrenia (Schizophrenia Working Group of the Psychiatric Genomics Consortium 2014). This SNP, however, does not intersect with any OCRs in the cell populations studied.…”
Section: Excitatory Neurons In the Cortex And Hippocampus Are Enrichementioning
confidence: 99%
“…rs11682175 achieves high PIPs with annotation in both loci (0.999 and 0.864 in rs75575209 and rs7596038, respectively) (Table S12). While not reported in the CLOZUK GWAS, rs11682175 has been significantly associated with major depression (Wray et al 2018), neuroticism (Nagel et al 2018), and schizophrenia (Schizophrenia Working Group of the Psychiatric Genomics Consortium 2014). This SNP, however, does not intersect with any OCRs in the cell populations studied.…”
Section: Excitatory Neurons In the Cortex And Hippocampus Are Enrichementioning
confidence: 99%
“…Traylor and colleagues (8) demonstrated that attempts to categorize patients with a complex disease into more homogeneous subgroups could have more power to elucidate the hidden heritability in a simulation study. Several studies on Alzheimer's disease, neuroticism, or asthma indicated that items or symptoms were to some degree more useful for identifying high-impact genetic factors than broadly defined diagnoses (9)(10)(11), although a study of ASD demonstrated modest effects of two-way stratification by individual symptoms (12). Additionally, medical researchers have begun to use machine learning methods (13), which is an artificial intelligence technique that can reveal masked patterns of data sets.…”
Section: Introductionmentioning
confidence: 99%
“…EPQ neuroticism contains two factors: mood instability (rapid fluctuations between high and low mood/energy and sudden/frequent shifts into low mood) and trait anxiety (nervousness, worry, and features of social anxiety such as self-consciousness and hypersensitivity to negative evaluation; Loo, 1995;Mor et al, 2008;Peters, Bowen, & Balbuena, 2019;Roger & Morris, 1991). Results from a recent genome-wide association study suggest these factors are genetically distinct (Nagel, Watanabe, Stringer, Posthuma, & Sluis, 2018). Anxiety is well represented in the NEO-PI-R and the Zuckerman-Kuhlman Personality Questionnaire, although mood instability is not (Maples, Miller, Hoffman, & Johnson, 2014;Miller & Pilkonis, 2006;Miller, Vachon, & Lynam, 2009;Zuckerman, 2002).…”
Section: Introductionmentioning
confidence: 99%